2016
DOI: 10.1016/j.jcmgh.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein Is a Pathogenic Mediator of Alcoholic Liver Disease and the Scavenger Hydralazine Is Protective in Mice

Abstract: Background & AimsAlcoholic liver disease (ALD) remains a major cause of morbidity and mortality, with no Food and Drug Administration–approved therapy. Chronic alcohol consumption causes a pro-oxidant environment and increases hepatic lipid peroxidation, with acrolein being the most reactive/toxic by-product. This study investigated the pathogenic role of acrolein in hepatic endoplasmic reticulum (ER) stress, steatosis, and injury in experimental ALD, and tested acrolein elimination/scavenging (using hydralazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 46 publications
5
42
0
1
Order By: Relevance
“…The hepatocyte exhibited loss of their normal architecture, intense cytoplasmic vacuolation, necrosis and hepatic steatosis. In fact, increased lipid peroxidation and depressed antioxidant status in the liver of rats receiving IMI caused oxidative stress which is known to induce endoplasmic reticulum (ER) stress [23]. Hepatic ER stress is accompanied by steatosis conforming to literature [24].…”
Section: Discussionsupporting
confidence: 76%
“…The hepatocyte exhibited loss of their normal architecture, intense cytoplasmic vacuolation, necrosis and hepatic steatosis. In fact, increased lipid peroxidation and depressed antioxidant status in the liver of rats receiving IMI caused oxidative stress which is known to induce endoplasmic reticulum (ER) stress [23]. Hepatic ER stress is accompanied by steatosis conforming to literature [24].…”
Section: Discussionsupporting
confidence: 76%
“…22 Acrolein was shown to induce protein adduct formation, and to mimic ethanol-induced ATF4/CHOP activation and cell death in cultured hepatocytes. 23 We found here that acrolein alone or in combination with ethanol dose-dependently induces acinar cell death, associated with XBP1s downregulation and CHOP upregulation (Supplementary Figure 6). Independently, a previous study showed that the CSE component hydroquinone causes apoptosis in retinal cells by upregulating CHOP and supressing XBP1s.…”
Section: Resultsmentioning
confidence: 64%
“…Concurrently, elevated acrolein staining correlates with the increased expression of GSTπ. GSTπ has been reported to metabolize acrolein and in a cell culture model, transfection of catalytically inactive GSTπ resulted in enhanced production of lipid peroxidation products as well 51,52 . In addition to effects on lipid peroxidation, polymorphisms in GSTπ are risk factors for NAFLD and decreased GSTπ expression are associated with carcinogenesis 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In the biliary disorder primary biliary cholangitis (PBC), GSTπ expression is decreased suggesting that GSTπ modulation is disease dependent. GSTπ has been reported to contribute to detoxification of reactive aldehydes in other hepatic diseases which overall suggests that the upregulation of GSTπ in end stage NASH samples is an attempt to mitigate damage that is occurring due to lipid peroxidation/protein carbonylation 52 .…”
Section: Discussionmentioning
confidence: 99%